Early Fresh Frozen Plasma Transfusion: Is It Associated With Improved Outcomes of Patients With Sepsis? - Qin, Xiaoyi; Zhang, Wei; Zhu, Xiaodan; Hu, Xiang; Zhou, Wei (Frontiers in Medicine, 2021)
Background: So far, no study has investigated the effects of plasma transfusion in septic patients, especially in terms of prognosis. Therefore, our purpose is to explore the association of early fresh frozen plasma (FFP) transfusion with the outcomes of septic patients. Methods: We performed a cohort study using data extracted from the Medical Information Mart for Intensive Care Ⅲ database (v1.4). External validation was obtained from the First Affiliated Hospital of Wenzhou Medical University, China. We adopted the Sepsis-3 criteria to extract patients with sepsis and septic shock. The occurrence of transfusion during the first 3 days of intensive care unit stay was regarded as early FFP transfusion. The primary outcome was 28-day mortality. We assessed the association of early FFP transfusion with patient outcomes using cox regression analysis. Furthermore, we performed sensitivity analysis, subset analysis and external validation to verify the true strength of the results. Results: After adjusting for the covariates in 3 models respectively, the significantly higher risk of death in the FFP transfusion group at 28 days (e.g. Model 2: HR = 1.361, P = 0.018, 95% CI = 1.054–1.756) and 90 days (e.g. Model 2: HR = 1.368, P = 0.005, 95% CI = 1.099–1.704) remained distinctly. Contrarily, the mortality increased significantly with the increase of FFP transfusion volume. The outcomes of septic patients with hypocoagulable state after early FFP transfusion were not significantly improved. Similar results can also be found in subset analysis of septic shock cohort. The results of external validation exhibited good consistency. Conclusions: Our study provides new understanding of the rationale and effectiveness of FFP transfusion for septic patients. After recognizing the evidences of risk-benefit and cost-benefit, it is important to reduce the inappropriate use of FFP and avoid unnecessary adverse transfusion reactions.